2016
DOI: 10.1007/s11255-015-1202-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary dorsal buccal mucosa graft urethroplasty for anterior urethral strictures in patients with lichen sclerosus

Abstract: Buccal mucosa is the most reliable graft for repairing anterior urethral strictures in patients with LS. Minimal complications are observed, even in cases of long stenosis completely afflicting anterior urethra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…Urethral strictures where the primary etiology other than BXO treated with buccal mucosa on lay graft as a single stage procedure shown similar results that is 82.8%, 87% and 90.6% success rate respectively in studies by G. barbagli et, al: Hussain Ahmad et, al : and Miodrag Acimovic et al, suggesting, irrespective of aetiology for anterior urethral stricture the results are good with buccal mucosa dorsal on-lay urethroplasty [18,19,20]. In a study by S.B Kulkarni et al, the overall success rate was 83.7% with a success rate of 86.5% for primary urethroplasty and 61.5% in patients in whom urethroplasty had previously failed.…”
Section: Issn-2321-127xmentioning
confidence: 80%
“…Urethral strictures where the primary etiology other than BXO treated with buccal mucosa on lay graft as a single stage procedure shown similar results that is 82.8%, 87% and 90.6% success rate respectively in studies by G. barbagli et, al: Hussain Ahmad et, al : and Miodrag Acimovic et al, suggesting, irrespective of aetiology for anterior urethral stricture the results are good with buccal mucosa dorsal on-lay urethroplasty [18,19,20]. In a study by S.B Kulkarni et al, the overall success rate was 83.7% with a success rate of 86.5% for primary urethroplasty and 61.5% in patients in whom urethroplasty had previously failed.…”
Section: Issn-2321-127xmentioning
confidence: 80%
“…However, in the series by Acimovic et al. , the fistula was managed by prolonged catheterization . The third recipient site complication was urethral stricture in one patient (2.9%) after 5 months at the proximal site of repair.…”
Section: Discussionmentioning
confidence: 98%
“…In accordance with Acimovic et al and Xu et al, who reported a fistula rate of 3.1% and 2.8%, respectively, one patient (2.9%) in the present study developed fistula. 7,17 The fistula was due to infection, which is considered to be a risk factor of graft surgery. The fistula was corrected surgically by simple closure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations